RANCANG BANGUN SISTEM PENGENDALI IRIGASI BERBASIS ANALISIS EVAPOTRANSPIRASI DENGAN KONTROLER PI - Suwoko Suwoko; Susilo Adi Widyanto (JURNAL TEKNIK MESIN, 2015)
Food is a basic requirement for life so that the availability is absolutely necessary of all time, while the source of the water decreases and becomes scarce during the dry season. One way to meet the water needs of plants properly is to calculate the crop evapotranspiration with Penman-Monteith equation. While the tools to realize the results of these calculations is to create an irrigation controllers system. Irrigation control system that is made has inputs from weather environment obtained with the sensor and has an output valve to drain the water. The type of valve used is linear and also installed on/off valve for comparison that performance. The main parameters are used as input air temperature, wind speed, relative humidity, and solar radiation. All parameters acquired digitally except solar radiation, solar radiation are acquired from correlation shaping using artificial neural networks algorithm with input temperature and light intensity. Artificial neural networks are used feedforward structure with neurons numbered 15. The controller used for each valve is on/off valve is controlled by the controller on/off and linear valves are controlled by a PI controller with constant Kp = 1.15 and Ki = 0.95.The test results are established neural network showed good results, where the error is 1.13%. The simulation results of the control system on/off produces an error of 0.68% and PI control system generates an error of 0.02%, while the application of control system on/off produces an error of 2.20%, and the PI control system generates an error of 1.74%